HUBUNGAN PERSEPSI GURU TERHADAP SUPERVISI AKADEMIK KEPALA SEKOLAH DAN KOMPETENSI SOSIAL GURU DENGAN KINERJA GURU - Mustova Joko Susilo; Baharuddin; Ibnu Muthi (Jurnal Riset Guru Indonesia, 2022)
This study aims to determine the relationship between teacher perceptions of principal supervision and teacher social competence on teacher performance in public and private elementary schools in Rawalumbu District, Bekasi City. The method used is the quantitative method, the sample taken is 100 teachers from 29 schools as respondents to the questionnaire. The sampling technique used in this research is random sampling. The instrument is a questionnaire. The results of the three hypotheses show that there is a jointly positive and significant relationship between teachers' perceptions of principal supervision and teacher social competence on teacher performance as indicated by the magnitude of the double correlation rcount = 0.986 while for rtable = 0.1654 it can be concluded that rcount > rtable = 0.986 > 0.1654 so that there is a positive and significant relationship jointly between teachers' perceptions of principal supervision and teacher social competence on teacher performance.